Diagnosis and Therapy of Female Genital Malformations (Part 1). Guideline of the DGGG, OEGGG and SGGG (S2k Level, AWMF Registry Number 015/052, May 2019) - Oppelt, Peter; Binder, Helge; Birraux, Jacques; Brucker, Sara; Dingeldein, Irene; Draths, Ruth; Eckoldt, Felicitas; Füllers, Ulrich; Hiort, Olaf; Hoffmann, Dorit; Hoopmann, Markus; Hucke, Jürgen; Korell, Matthias; Kühnert, Maritta; Ludwikowski, Barbara; Mentzel, Hans-Joachim; mon OʼDey, Dan; Rall, Katharina; Riccabona, Michael; Rimbach, Stefan; Schäffeler, Norbert; Shavit, Sandra; Stein, Raimund; Utsch, Boris; Wenzl, Rene; Wieacker, Peter; Zeino, Mazen (Geburtshilfe und Frauenheilkunde, 2021)
Objectives Female genital malformations may take the form of individual entities, they may involve neighboring organs or they may occur in the context of complex syndromes. Given the anatomical structures of the vulva, vagina, uterus and adnexa, the clinical picture of malformations may vary greatly. Depending on the extent of the malformation, organs of the urinary system or associated malformations may also be involved.Methods This S2k-guideline was developed by representative members from different medical specialties and professions as part of the guidelines program of the DGGG, SGGG and OEGGG. The recommendations and statements were developed using a structured consensus process with neutral moderation and voted on.Recommendations The guideline is the first comprehensive presentation of the symptoms, diagnosis and treatment options for female genital malformations. Additional chapters on classifications and transition were included.
Keywords: guideline; genital malformation; genital reconstruction; MRKH; vaginal septum; subseptate uterus; bladder exstrophy; cloacal malformation